Optimisation of 3D profiled woven composite structures - Spackman, George (2024)
Composite 3D woven components have been used in aerospace components because of their improved through-thickness properties and ability to be woven integrally in near-net shape. The complex stress conditions and long time required to manufacture and test physical specimens means that the relationship between the reinforcement’s weaving pattern and the mechanical behaviour of 3D woven composite T-joints is not well understood. With approximately 3.6 million possible combinations of weft yarn configurations alone for a textile with 10 weft layers, an exhaustive search of the design space is not possible. To resolve this, the aim of this project was to apply optimisation algorithms to 3D woven profiled structures such as T-Joints. Previous geometry modelling work in the literature had provided a framework to produce these models but were done by-hand using a manual process.